The Legal Validity of Mediation in Marriage Annulment Cases Without the Respondent’s Presence Under Supreme Court Regulation No. 1 of 2016 - Basri, Jelyna; Saepullah, Usep; Yuniardi, Harry (Sakina: Journal of Family Studies, 2025)
This study examines the legal validity of mediation in marriage annulment cases conducted without the respondent’s presence, focusing on its conformity with the provisions of Supreme Court Regulation (PERMA) No. 1 of 2016 on Court-Annexed Mediation Procedures. Employing a normative juridical research method with statutory and conceptual approaches, the analysis draws upon primary legal sources, including PERMA No. 1 of 2016, Law No. 1 of 1974 on Marriage, and the Compilation of Islamic Law (KHI), as well as relevant religious court decisions. Secondary sources consist of scholarly books, legal literature, and journal articles addressing mediation in marriage annulment and divorce cases. The findings indicate that, although marriage annulment proceedings are exempt from mandatory mediation, some religious courts still conduct mediation as a peace-seeking effort. However, declaring mediation successful in the absence of the respondent contravenes the fundamental principle of active party participation, undermines legal certainty, and potentially diminishes the protection of the rights of absent parties. The study concludes that mediation in annulment cases without the respondent’s presence lacks strong legal validity under PERMA No. 1 of 2016, and may generate procedural injustice and uncertainty in religious court practice. It recommends stricter judicial adherence to mediation procedures, particularly regarding the mandatory presence requirement when mediation is undertaken, even in exempt cases.